2019
DOI: 10.1249/mss.0000000000001786
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Napping on Alertness, Cognitive, and Physical Outcomes of Karate Athletes

Abstract: Purpose It has been suggested that napping is the best recovery strategy for athletes. However, researches on the impacts of napping on athletic performances are scarce. The aim of this study was to determine the effects of a 30-min nap after a partial sleep deprivation, or a normal night condition, on alertness, fatigue, and cognitive and physical outcomes. Methods Thirteen national-level male karate athletes were randomized to experience nap and no-na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
95
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(103 citation statements)
references
References 31 publications
5
95
2
Order By: Relevance
“…Our results were consistent with those reported by other studies confirming the beneficial effect of napping on cognitive [ 11 , 14 , 16 ] and physical performance [ 11 , 12 , 13 , 15 , 16 , 17 , 28 , 29 , 31 , 32 ], independent of the previous night’s sleep. For example, following a normal night sleep, it has been shown that (i) a 25-min nap opportunity enhanced performance during the 5mSRT [ 12 ], (ii) a 25-min, 35-min and 45-min nap opportunity increased physical performance during the 5mSRT [ 13 ], (iii) a 35-min and 45-min nap opportunity enhanced 5 jump performance [ 11 ], and (iv) a 45-min [ 11 ] and 90-min [ 10 ] nap improved attention estimated by the digit cancelation test (DCT).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results were consistent with those reported by other studies confirming the beneficial effect of napping on cognitive [ 11 , 14 , 16 ] and physical performance [ 11 , 12 , 13 , 15 , 16 , 17 , 28 , 29 , 31 , 32 ], independent of the previous night’s sleep. For example, following a normal night sleep, it has been shown that (i) a 25-min nap opportunity enhanced performance during the 5mSRT [ 12 ], (ii) a 25-min, 35-min and 45-min nap opportunity increased physical performance during the 5mSRT [ 13 ], (iii) a 35-min and 45-min nap opportunity enhanced 5 jump performance [ 11 ], and (iv) a 45-min [ 11 ] and 90-min [ 10 ] nap improved attention estimated by the digit cancelation test (DCT).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies are limited by the lack of an objective measurement of the previous night’s sleep [ 11 , 12 , 13 , 15 , 16 , 17 , 28 ], which may confound their results. In this study, we confirmed total time sleep before each condition via the use of actigraphy, similar to previous work [ 14 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…To the best of the authors’ knowledge, this is the first study investigating the effect of a nap opportunity during Ramadan observance on physical and cognitive performance. Although positive effects have been observed on physical performance (i.e., increase of TD and BD after N35 in the all experimental sessions) and cognitive performance (i.e., improvement of attention after N35 at DR and AR), previous studies show that napping might improve physical [ 24 , 25 , 26 , 27 , 28 , 41 ] and cognitive [ 28 , 41 ] performance. The non significant effect of the nap opportunity on some parameters may be related to duration.…”
Section: Discussionmentioning
confidence: 87%